TRANSPARANSI PEMERINTAH DESA DALAM PENGELOLAAN KEUANGAN DESA TEGALREJO KECAMATAN TUGUMULYO KABUPATEN MUSI RAWAS - Wendi Aji Saputra; Eva Kurnia Farhan (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2021)
This study aims to to know the openness of the village administration in the management of the year 2015-2017 village funds. The village administration be obliged to run village finance who are managed based on azas transparent, accountable, participatory and performed with raise awareness and discipline of the budget. Transparency in financial management village by the government village tegalrejo can be said overall transparent, as gave has provided information about the planning process and implementation, to the council has included village funds some sections of the community. And for the village funds in development activities have involving the public. Access for the willingness to know about the use of funds village that had been used, the village administration tegalrejo have provided information in writing on the bulletin board village